Paesaggi del bel paese, dal viaggio al turismo - Corsani, Gabriele (Ri-Vista. Research for landscape architecture, 2015)
The link between Northern and Southern Italy was created at the beginning of the decade following the national unity (1861) with the laying of the first railway network. Italian literary reviews, reports and collections of books devoted to the discovery of the ethnographic and physical features of the new Italian Kingdom spread quickly. At the same time, journals and memories of individual trips confirmed the hints given by the relevant literature and provided new tips about the most celebrated tourist destinations which were further developed by the suggestions of the foreign writers living in Italy. In this literature, landscape descriptions depict the face of a big variety of shapes, colours and habits as well as the sense of the national belonging. This type of interpretation showed such features until the 1960s when it was overthrown by the deal of mass tourism.